Integrasi Teknologi IoT pada Sistem CRM untuk Meningkatkan Kepuasan dan Retensi Pelanggan - Ferry Cahyadi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The Internet of Things (IoT) has become one of the leading technologies in digital transformation, including in customer relationship management (CRM). This article discusses how IoT integration in CRM systems can improve customer satisfaction and retention through real-time data collection, service personalization, and data-driven decision making. With a literature study and implementation analysis, this research shows that IoT technology can provide deeper insight into customer behavior, improve operational efficiency, and create a more satisfying customer experience.